PENGARUH nPENGGUNAANnMEDIAnPOWER POINTnTERHADAP HASILnBELAJAR RUPA SISWAnKELAS VII SMPnNEGERI 23 PADANG - Ulfa Khairani, Dr. Ramalis Hakim, M.Pd. (Serupa The Journal of Art Education, 2019)
This research havena purposento develop the work creativityof “Seni Rupa” with use contextual approach to student grade VII4 and VII8. The result of this research show that the value average which use contexual apporoach is about 81.33 and the one which use conventional method have value average about 72.90. This is show up that the creativity differences in worksmin the fine art. Independent influence to dependent variable that show that value t count = 4.077 and t table = 2.048 > 0.05 take positive effect to the significant off work in the fine art sector.Keywordn: development,ncreativity,ncontextualnapproach